Combination therapy with amelotеx and compligamv in patients with osteoarthrosis - Tatyana Anatolyevna Vygovskaya (Современная ревматология)
Objective: to study the efficiency of combined use of CompligamV (a vitamin B complex group) and Amelotex (meloxicam) in the complex treatment of osteoarthrosis (OA). Subjects and methods. Thirty patients (25 women and 5 men) aged 49 to 83 years with a disease history of 2 to 20 years (mean 6.8 years) mainly with involvement of knee, ankle, and shoulder joints, X-ray stage II-IV disease (after A. Larsen). OA was complicated by reactive synovitis of the knee and ankle joints in 48.3% of the patients. The minimal course of therapy for OA was 15 days: Amelotex (15 mg, intramuscular) and CompligamV were concurrently administered for the first 5 days; CompligamV therapy was continued on the 6th to 15th days. Therapeutic effectiveness was evaluated from clinical changes ranging in 0 to 5 scores by the Oswestry questionnaire (rest pain, movement pain, and limited active and passive movements). A clinical relevant effect was stated when the scores in each section were decreased by 6 scores or more. Furthermore, the data from the health status scale, the pain intensity scale, and the risk for gastrointestinal complications were assessed by the Singh index. Results. There were clinical improvements (reduced signs of arthritis, increased exercise endurance, relieved pain syndrome) during combination therapy with Amelotex and CompligamV. Conclusion. The rapid onset and long duration of the action of combination therapy with Amelotex and CompligamV positively affected the patients' status and could reduce the cost of treatment